2023
DOI: 10.1021/acs.est.3c01307
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Microplastics by ZnO Nanoparticles with Resulting Cellular and Subcellular Responses

Abstract: Both zinc oxide nanoparticles (ZnO NPs) and microplastics (MPs) were extracted from one commercial sunscreen, while other ingredients were removed based on the “like dissolves like” principle. MPs were further extracted by acidic digestion of ZnO NPs using HCl and characterized as spherical particles of approximately 5 μm with layered sheets in an irregular shape on the surface. Although MPs were stable in the presence of simulated sunlight and water after 12 h of exposure, ZnO NPs promoted the photooxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Elemental composition analysis revealed marked differences in polymers, with higher proportions of Si (31.6%) and O (31.6%) atoms in the smooth-surfaced microbead (referred to as Si-32), compared to limited Si (5.1%) and lower O (13.6%) atoms in the rough-surfaced microbead (referred to as Si-5, Figures c and S14). The result was consistent with our previous study, where the silicone-based cross-polymer and acrylates copolymer were identified as the main components in sunscreen-extracted MPs, corresponding to Si-32 and Si-5, respectively. Silicone is commonly used to improve the UV resistance of epoxy resins, which could explain the higher resistance of Si-32 to phototransformation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Elemental composition analysis revealed marked differences in polymers, with higher proportions of Si (31.6%) and O (31.6%) atoms in the smooth-surfaced microbead (referred to as Si-32), compared to limited Si (5.1%) and lower O (13.6%) atoms in the rough-surfaced microbead (referred to as Si-5, Figures c and S14). The result was consistent with our previous study, where the silicone-based cross-polymer and acrylates copolymer were identified as the main components in sunscreen-extracted MPs, corresponding to Si-32 and Si-5, respectively. Silicone is commonly used to improve the UV resistance of epoxy resins, which could explain the higher resistance of Si-32 to phototransformation.…”
Section: Resultssupporting
confidence: 93%
“…Annually, an estimated 8–12 million metric tons of plastics are introduced into the ocean, resulting in the pervasive presence of microplastics (particles smaller than 5 mm, MPs). , Due to their size and buoyancy, MPs resemble the natural prey of zooplankton and are readily ingested, becoming incorporated within the zooplankton community. , Although MPs exhibit high bioavailability and bioaccumulation in zooplankton, their presence is generally considered innocuous due to their stable and inert characteristics. , Particles with a synthetic composition, solid state, and insolubility assembled to MPs were successfully extracted from commercial sunscreens, indicating an unavoidable interaction between MPs and ZnO UV filters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…113 In addition to the combined exposure of multiple nanomaterials, 114 ZnO NPs can also adsorb with microplastics 115 but are limited by Zn 2+ , 116 as well as stimulate surface oxidation and degradation of microplastics. 117 Considering that ZnO NPs can act as both bioregulator products and exogenous nano-pollutants, the unknown risks to plants induced by exposure to multiple systems may be either toxicity mitigation or toxicity exacerbation (Table 1), implying that the field needs to be supported by more adequate research in the future.…”
Section: Uncertain Ecological Risks Of Np Composite Systems To Plantsmentioning
confidence: 99%
“…In this regard, primary MPs are widely found in cosmetics and personal care products (PCPs). Polyethylene (PE)-derived MPs have been detected in some commercially available skin cleansing products and scrubs at concentrations as high as 4.2–111.2 mg/mL, resulting in a severe risk of MPs exposure in the population. Secondary MPs are usually formed by the physical, chemical, and biological decomposition of large plastic fragments . Numerous studies have shown that MPs exhibit global transport properties and are found in almost all environmental media, inducing severe ecological and population health crises. , The toxicity of MPs can be divided into direct toxicity and compound toxicity.…”
Section: Introductionmentioning
confidence: 99%